Fitotoxicidade e eficácia de extratos aquosos aplicados no manejo de plantas daninhas em culturas de verão - Reik, Gabriele Gaiki (2016)
Allelopathy comprises the direct or indirect effect promoted by one plant on the other, through allelochemicals released into the environment. These allelochemicals may interfere with seed germination and the development of neighboring plants. This natural phenomenon has been researched with the aim of discovering new molecules capable of controlling the presence of weeds and later reducing and / or replacing the use of pesticides by natural herbicides. In this sense, the present study aimed to evaluate the allelopathic potential of Eragrostis planus (Anonimae), Cyperus rotundus (Teraica) and Avena strigosa (Black oats) in the germination and initial growth of Bidens pilosa (black stingray), Euphorbia heterophylla (Dairy), Conyza sp. (Buva), Digitaria horizotalis (milan), Zea mays (corn), Glycine max (soybean) and Phaseolus vulgaris (beans). For the germination tests, six concentrations of aqueous extract (10%, 30%, 50%, 70% and 90%) diluted with distilled water were used, in addition to the control obtained with distilled water (0%) and extract Gross (100%). For each test the extracts were evaluated separately, and four replicates were performed with 20 seeds in each plate. The germination percentage (PG%), germination velocity index (IVG), mean root length (CMR) and mean shoot length (CMPA) were analyzed using the following data. It was noticed that the extracts of black oats, tiririca and anonni grass promoted interference in seed germination, initial shoot and root growth of some species tested. Among the interferences was identified reduction and / or inhibition of seed germination, presence of irregular radicles and necrosis in seedlings. In the vast majority, the interference occurred in the presence of the crude extract (100%). Briefly, it was concluded that the extracts applied in the germination tests present allelopathic potential and influence the germination and initial growth of the weed seedlings and cultivated in the test according to the concentration applied and the parameter evaluated.